2020
DOI: 10.20452/pamw.15631
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic correlates and biochemical profiles of smokers in Poland: cross-sectional study

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…As expected, poor lifestyle index rates were significantly higher among persons with lower educational attainment. This finding is in line with other authors results suggesting that those with elementary or less than college degrees exhibit unhealthy behaviour profiles [40][41][42]. According to Zujko et al (2020) higher socioeconomic status was significantly associated with a more favourable lifestyle, better objective health outcomes and better dietary habits (including a higher intake of dietary antioxidants) [13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As expected, poor lifestyle index rates were significantly higher among persons with lower educational attainment. This finding is in line with other authors results suggesting that those with elementary or less than college degrees exhibit unhealthy behaviour profiles [40][41][42]. According to Zujko et al (2020) higher socioeconomic status was significantly associated with a more favourable lifestyle, better objective health outcomes and better dietary habits (including a higher intake of dietary antioxidants) [13].…”
Section: Discussionsupporting
confidence: 89%
“…According to Zujko et al (2020) higher socioeconomic status was significantly associated with a more favourable lifestyle, better objective health outcomes and better dietary habits (including a higher intake of dietary antioxidants) [13]. Also a recent report of Zagozdzon et al (2020) revealed substantial differences regarding socioeconomic characteristics between smokers and non-smokers in Poland [41]. There was a statistically significant inverse relationship between income and smoking and persons living in towns were more likely to smoke than those living in rural areas [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled mean levels of apolipoprotein B were 1.06 ± 0.009 g/L in smokers and 0.98 ± 0.007 g/L in nonsmokers. The meta-analysis of apolipoprotein B levels in smokers versus nonsmokers included 40 studies and 63 estimates [23] , [24] , [27] , [28] , [29] , [30] , [32] , [34] , [35] , [37] , [38] , [39] , [40] , [41] , [42] , [44] , [45] , [46] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [62] , [70] . Increased levels of apolipoprotein B were found in smokers using the fixed-effects model (mean difference= 0.056, 95% CI: 0.053, 0.059 g/L, I 2 =95%).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled mean ratios of apolipoprotein B to AI were 0.62 ± 0.002 in smokers and 0.65 ± 0.001 in nonsmokers. The meta-analysis assessing the effects of smoking on the apolipoprotein B: AI ratio included 31 studies with 46 estimates [23] , [24] , [27] , [28] , [29] , [30] , [32] , [34] , [35] , [37] , [38] , [39] , [40] , [41] , [42] , [44] , [45] , [46] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [62] , [70] . The fixed-effects model showed an increased ratio in smokers (mean difference= 0.047, 95% CI: 0.047, 0.048 g/L, I 2 =99%).…”
Section: Resultsmentioning
confidence: 99%